2022
DOI: 10.3390/metabo12020140
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic CYP3A4 Enzyme Compensatively Maintains Endogenous Geranylgeranoic Acid Levels in MAOB-Knockout Human Hepatoma Cells

Abstract: Geranylgeranoic acid (GGA), developed as a preventive agent against second primary hepatoma, has been reported to be biosynthesized via the mevalonate pathway in human hepatoma-derived cells. Recently, we found that monoamine oxidase B (MAOB) catalyzed the oxidation of geranylgeraniol (GGOH) to produce geranylgeranial (GGal), a direct precursor of endogenous GGA in hepatoma cells, using tranylcypromine, an inhibitor of MAOs, and knockdown by MAOB siRNA. However, endogenous GGA level was unexpectedly unchanged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, it has been shown that hepatic MAOB is involved in the oxidation reaction of GGOH to GGal, as MAOB inhibitor treatment decreased the intracellular GGA content and knockdown of the MAOB gene using a specific siRNA-inhibited GGA synthesis from GGOH ( 43 ). On the other hand, intracellular GGA content was maintained at the same level in MAOB-KO cells as in wild-type cells, indicating that CYP3A4, as a backup enzyme of MAOB, is involved in the oxidation of GGOH to GGal, as shown by experiments using inhibitors and siRNA ( 44 ). The oxidation of GGal to GGA is NAD(P) + -dependent and is catalyzed by ALDH, a nonspecific enzyme.…”
Section: Biosynthesis Of Gga In Human Hepatoma Cellsmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, it has been shown that hepatic MAOB is involved in the oxidation reaction of GGOH to GGal, as MAOB inhibitor treatment decreased the intracellular GGA content and knockdown of the MAOB gene using a specific siRNA-inhibited GGA synthesis from GGOH ( 43 ). On the other hand, intracellular GGA content was maintained at the same level in MAOB-KO cells as in wild-type cells, indicating that CYP3A4, as a backup enzyme of MAOB, is involved in the oxidation of GGOH to GGal, as shown by experiments using inhibitors and siRNA ( 44 ). The oxidation of GGal to GGA is NAD(P) + -dependent and is catalyzed by ALDH, a nonspecific enzyme.…”
Section: Biosynthesis Of Gga In Human Hepatoma Cellsmentioning
confidence: 92%
“…Expectedly, treatment of MAOB -KO (Hep3B/ MAOB -KO) cells with the cytochrome P450 enzyme activity pan-inhibitors 1-aminobenzotriazole (ABT) or bergamottin (BG) resulted in a concentration-dependent decrease in endogenous GGA levels (IC 50 10.9 μM for ABT, 7.5 μM for BG) ( 44 ). On the other hand, in the WT (Hep3B/ MAOB -WT) cells expressing the MAOB gene, no decrease in endogenous GGA concentration was observed with these inhibitors, indicating that cytochrome P450 enzymes are involved in the synthesis of endogenous GGA [XI] only in MAOB -KO cells.…”
Section: Oxidation Of Geranylgeraniol Requires Molecular Oxygenmentioning
confidence: 99%
“…Further in vitro and in vivo metabolic tests of astemizole, a common CYP2J substrate, revealed that in knockout rats, CYP2J was functionally inactive [21]. In 2022, geranylgeranoic acid (GGA) responsible for inhibitors against second primary hepatoma were unexpectedly maintained after the KO of monoamine oxidase B (MAOB) cells by CRISPR-Cas9 [22]. After being investigated, the authors concluded that CYP3A4 expression was increased after MAOB-KO and CYP3A4 were found to act as alternative oxidases to geranylgeraniol subsequently maintaining the GGA.…”
Section: Introductionmentioning
confidence: 99%